Increased activity of mesenchymal ALK2‐BMP signaling causes posteriorly truncated microglossia and disorganization of lingual tissues. Issue 1 (30th September 2019) - Ishan, Mohamed; Chen, Guiqian; Sun, Chenming; Chen, Shi‐You; Komatsu, Yoshihiro; Mishina, Yuji; Liu, Hong‐Xiang
Summary: Proper development of taste organs including the tongue and taste papillae requires interactions with the underlying mesenchyme through multiple molecular signaling pathways. The effects of bone morphogenetic proteins (BMPs) and antagonists are profound, however, the tissue‐specific roles of distinct receptors are largely unknown. Here, we report that constitutive activation (ca) of ALK2‐BMP signaling in the tongue mesenchyme (marked by Wnt1‐Cre ) caused microglossia—a dramatically smaller and misshapen tongue with a progressively severe reduction in size along the anteroposterior axis and absence of a pharyngeal region. At E10.5, the tongue primordia (branchial arches 1–4) formed in Wnt1‐Cre/caAlk2 mutants while each branchial arch responded to elevated BMP signaling distinctly in gene expression of BMP targets ( Id1, Snai1, Snai2, and Runx2 ), proliferation ( Cyclin‐D1 ) and apoptosis ( p53 ). Moreover, elevated ALK2‐BMP signaling in the mesenchyme resulted in apparent defects of lingual epithelium, muscles, and nerves. In Wnt1‐Cre/caAlk2 mutants, a circumvallate papilla was missing and further development of formed fungiform papillae was arrested in late embryos. Our data collectively demonstrate that ALK2‐BMP signaling in the mesenchyme plays essential roles in orchestrating various tissues for proper development of the tongue and its appendages in a region‐specific manner.